Peningkatan Kemampuan Menyimpulkan Isi Cerita rakyat melalui Model Pembelajaran Batangbesi - Agustiani, Iis; M, Mainilawati; H, Hetilaniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Regarding the problem of learning models, research researchers need to carry out class action research (PTK), so that learning outcomes can be improved, as expressed by Kasboillah (2008:13), that class action research (PTK) is important is one of the teacher's efforts to practice in various forms of activities which is carried out to increase the improvement of learning through approaches carried out directly by researchers. In this way, through this class action research activity the aim is to measure students' interests and abilities and find appropriate solutions to overcome the problems and difficulties faced by students in learning Indonesian, especially in mathematics. Summarize the contents of people's stories. This research uses the Class Action methodology. PeÃ¬neÃ¬liti by carrying out learning actions in class. Based on the results of the observations, the researchers concluded that the average answer was